PEMBELAJARAN VOKAL SINDENAN GAYA JAWATIMURAN DENGAN MODEL PROJECT BASED LEARNING (PJBL) DI JURUSAN KARAWITAN SMKN 12 SURABAYA: Bahasa Indonesia - Dhea Ahmada Putri; handayaningrum, Warih (Solah, 2025)
Initially, the learning conditions in the East Javanese style vocal sindenan subject in the Karawitan Department of SMKN 12 Surabaya were felt to be ineffective. This prompted the vocal teacher to use the Project-Based Learning (PjBL) model. This study employed qualitative and descriptive methods. Data collection methods included observation, interviews, and documentation. The study involved karawitan art teachers, vocal teachers, and 12th-grade Karawitan students at SMKN 12 Surabaya. Data analysis was conducted by presenting the data and drawing conclusions. The results of the application of the project-based learning (PjBL) model show 5 learning outcomes, namely: 1) Students can understand the characteristics of East Javanese style sinden vocals, 2) Students are able to perform East Javanese style sinden vocals according to the rules, 3) Students are able to innovate in the form of developing East Javanese style sinden vocals, 4) Students are able to appreciate the process, and 5) Students are able to implement East Javanese style sinden vocals in real life.Time constraints, a lack of learning support resources, and differences in the vocal abilities of the students’ singers are some of the challenges encountered. Therefore, the project- based learning model can be successfully applied in East Javanese style vocal singing lessons, especially in efforts to preserve traditional arts by using innovative and participatory learning stages.